The respiratory health of urban indigenous children aged less than 5 years: study protocol for a prospective cohort study - Hall, Kerry K. (BMC Pediatr, 2015)
BACKGROUND: Despite the burden of acute respiratory illnesses (ARI) among Aboriginal and Torres Strait Islander children being a substantial cause of childhood morbidity and associated costs to families, communities and the health system, data on disease burden in urban children are lacking. Consequently evidence-based decision-making, data management guidelines, health resourcing for primary health care services and prevention strategies are lacking. This study aims to comprehensively describe the epidemiology, impact and outcomes of ARI in urban Aboriginal and Torres Strait Islander children (hereafter referred to as Indigenous) in the greater Brisbane area. METHODS/DESIGN: An ongoing prospective cohort study of Indigenous children aged less than five years registered with a primary health care service in Northern Brisbane, Queensland, Australia. Children are recruited at time of presentation to the service for any reason. Demographic, epidemiological, risk factor, microbiological, economic and clinical data are collected at enrolment. Enrolled children are followed for 12 months during which time ARI events, changes in child characteristics over time and monthly nasal swabs are collected. Children who develop an ARI with cough as a symptom during the study period are more intensely followed-up for 28 (±3) days including weekly nasal swabs and parent completed cough diary cards. Children with persistent cough at day 28 post-ARI are reviewed by a paediatrician. DISCUSSION: Our study will be one of the first to comprehensively evaluate the natural history, epidemiology, aetiology, economic impact and outcomes of ARIs in this population. The results will inform studies for the development of evidence-based guidelines to improve the early detection, prevention and management of chronic cough and setting of priorities in children during and after ARI. TRIAL REGISTRATION: Australia New Zealand Clinical Trial Registry Registration Number: 12614001214628. Registered 18 November 2014